Strategi Penjualan Pabrik Tahu Sumedang dengan Pendekatan Pemasaran Islam di Kp. Pamulihan Ds. Ciporeat Kab. Bandung - Salam, Mochamad Fadlani; Yanti, Ricaingke; Hakim, Azzam Luqman; Akbar, Fachrul Rizkian (Future Academia : The Journal of Multidisciplinary Research on Scientific and Advanced, 2025)
Conventional marketing approaches often prioritize profit alone without regard to moral and ethical aspects. This encourages the need for an alternative marketing approach that is more ethical, one of which is through the application of Islamic marketing principles. This study aims to identify the sales strategies applied by tofu factories in Sumedang and evaluate the implementation of Islamic marketing principles in their marketing activities. The research method used is qualitative with a descriptive approach, through in-depth interviews and direct observation of business actors and the marketing process. The results showed that the sales strategy of Sumedang tofu factories has considered aspects of consumer trust, product quality, and good relations with business partners. In addition, some Islamic marketing principles such as information transparency, honesty in transactions, and avoidance of exploitative practices have begun to be applied even though they have not been explicitly realized as part of Islamic teachings. Thus, the integration of Islamic marketing values has the potential to increase consumer trust and business sustainability in the traditional food industry.